Intestinal parasites in howler monkeys Alouatta palliata (Primates: Cebidae) of Costa Rica - Chinchilla Carmona, Misael (2005)
Fecal samples of 102 howler monkeys (Alouatta palliata) from several sites of Costa Rica were studied for intestinal parasites. The zones studied were: Central Valley (San Ramón, Alajuela), Central Pacific (Chomes and Manuel Antonio National Park, Puntarenas), North Pacific (Palo Verde Park and Playa Potrero, Guanacaste), Chira Island in the Nicoya Gulf and Caribean area (Cahuita, Limón). Animals were anesthetized with dards containing Telazol in order to collect the fecal material; some monkeys defecated spontaneously and others by direct stimulation. Samples were studied in saline solution (0.85%) and a Iodine solution, or stained with Haematoxylin. The material was also cultured in Dobell culture medium to determine the presence of amoeba and flagellates. Strongyloides, Controrchis, Trypanoxyuris genera were found in 3.4% of the samples. In addition 16.7% to 80% of the animals showed protozoa infection with Endolimax, Entamoeba, Trichomonas and Giardia. It is discussed the relationships of parasite infection with environmental conditions, animal population and human presence, specially in the monkey conservation programs point of view.